RE-EXAMINATION OF THE SUSPECT IN THE PROCESS OF SUBMITTING EVIDENCE AT THE CIREBON CITY DISTRICT ATTORNEY'S OFFICE - Dhea Wardah Aulia; Abdul Azis Mustofa; Uba Dawan Mubarok; Waluyadi Waluyadi (Jurnal Abdisci, 2025)
Abstract: Background. A good law enforcement process is the highest hope for the community, especially for justice seekers entangled in legal problems. Problems in the law enforcement process often occur at the pre-prosecution level. Aims. This study aims to analyze the process of re-examination by the Public Prosecutor against the suspect when handing over evidence at the Cirebon City District Attorney's Office. In Indonesian criminal procedure law, this process is regulated by Law No. 8 of 1981 concerning the Criminal Procedure Code and Law No.11 of 2021 concerning Amendments to Law No.16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia. Methods. This research identifies two main problems: (1) the juridical review of the re-examination by the public prosecutor, and (2) whether the process falls under the category of additional examination. The research method used in this research is empirical juridical. The legal research approach is conducted through literature study and interviews. Result. The results of this study indicate that the re-examination conducted by the Public Prosecutor is not part of the additional examination as stipulated in Article 30 paragraph (1) letter e of Law No. 16 of 2004. Implementation. Therefore, the actions of the Public Prosecutor in the process of handing over evidence are categorized as administrative and substantive research in the standard procedure before the case submission to the prosecution stage.